Political communication in Chinese history: the influence of confucianism on centralized monarchy - Zuzana Budiská; Chi Wang (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
The purpose of this article is to analyze the influence of Confucianism on the centralized monarchy in Chinese history. This article adopts literature research method and interdisciplinary research method. Confucianism catered to the centralization of the monarchy in Chinese history.